Pengaruh Mata Kuliah Metodologi Penelitian terhadap Karya Tulis Ilmiah Mahasiswa PGSD Stambuk 2022 Universitas Negeri Medan - Dhea Divana Anggreni Br Kaban; Tiara Sauna Br Sembiring; Nurleli Hasibuan; Syahrial Syahrial (Lembaga Pengembangan Kinerja Dosen, 2025)
The ability to write scientific papers is a competency that students must have in the academic world. The Research Methodology course plays an important role in improving this skill, because it provides an understanding of the basic concepts of research, methods, and systematic data analysis. This study aims to analyze the effect of the Research Methodology course on the scientific writing skills of PGSD Stambuk 2022 students, State University of Medan. The research method used is a quantitative approach with simple linear regression analysis. Data were collected through questionnaires distributed to students taking the course. The results of the study showed that the Research Methodology course had a significant influence on students' scientific writing skills with a coefficient of determination (R Square) of 63.8%. This shows that a good understanding of research methodology can help students in compiling scientific papers more systematically and with quality.